Scalp hair whorl. Epidemiological study in 510 subjects. - Milano, A.; de Palma, M. (European Journal of Pediatric Dermatology, 2013)
The scalp hair whorl is a circular distribution of hair that revolves around an axis. The majority of subjects has a single whorl of hair located in the parietal region below the vertex and in the hair whorl usually revolves clockwise. There are anomalies of number, location and rotation of the hair whorl. These anomalies have been made in the past in relation with being left-handed, with the dominant location of the center of the language in cerebral hemispheres, with sexual orientation and, what is more important for the pediatric dermatologist, with some inherited disorders, especially when associated with mental retardation. Here were reported preliminary data from a study of 510 children affected or not affected by skin diseases. The most common abnormality is the presence of an additional frontal whorl detected in 7.8% of our population. Anomalies of whorls were more frequent in males and in children with inherited skin disorders.